Growth and characterization of dual ion beam sputtered Cu2ZnSn(S, Se)4 thin films for cost-effective photovoltaic application. (1st December 2016) - Sengar, Brajendra S.; Garg, Vivek; Awasthi, Vishnu; Aaryashree,; Kumar, Shailendra; Mukherjee, C.; Gupta, Mukul; Mukherjee, Shaibal
Highlights: CZTSSe has been successfully deposited by DIBS technique using quintuple target without annealing or selenization. The thin films grown at Tsub = 300 °C is Cu poor and Zn rich and Sulfur confirmed by EDX results. The optical coefficient of all CZTSSe thin films are evaluated to be >4 × 10 4 cm −1 . The values of band gap of CZTSSe are found to be in the range of 1.23–1.70 eV. Abstract: A systematic growth optimization of Cu2 ZnSn(S, Se)4 (CZTSSe) thin films by dual ion beam sputtering system from a single CZTSSe target is presented. It is observed that the ratio of Cu/(Zn + Sn) varies from 0.86 to 1.5 and that of (S + Se)/metal varies between 0.62 and 0.97 when substrate temperature (Tsub ) is increased from 100 to 500 °C. The crystal structure of all CZTSSe films are identified to be preferentially (1 1 2)-oriented, polycrystalline in nature, and without the existence of secondary phases such as Cu2 (S, Se) or Zn(S, Se). The full-width at half-maximum of (1 1 2) diffraction peak is the minimum with a value of 0.12° and the maximum crystallite size 75.11 nm for CZTSSe grown at 300 °C. Morphological investigation reveals the achievement of the largest grain size at Tsub = 300 °C. The band gap of CZTSSe thin films at room temperature, as determined by spectroscopic ellipsometry, varies from 1.23 to 1.70 eV, depending on Tsub . The optical absorption coefficient of all CZTSSe thin films is >10 4 cm −1 .